Water and creep feed consumption by piglets and the effects of solid feed and water restriction on performance in early life - Kuan, K. K.; Mak, T. K. (Universiti Pertanian Malaysia, 1979)
Piglets provided 'with 'water from day old were observed to consume small amounts (58 g/day),. at this early age and intake of solid feed began during the second 'Week of life. Average daily gain of pigs following weaning was significantly greater when the animals 'Were provided offered creep feed from day old and at the beginning of the second week compared to animals that were only offered creep feed commencing at three weeks of age. The increase in average daily gain was due to increased consumption of solid feed following weaning